Five steps to beating ransomware's five-minute warning. Issue 11 (November 2020) - Lock, Matt
Abstract : When ransomware strikes an IT network, there is precious little time to react. Indeed, some accounts by IT professionals put it at less than five minutes. At that speed it is next to impossible using manual methods to stop ransomware propagating throughout an IT system. Firms need to work on the assumption that they will be attacked at some point, and so need to put in place measures that will help them survive an attack with as little damage as possible, says Matt Lock at Varonis. When ransomware strikes an IT network there is precious little time to react. Indeed, some accounts by IT professionals put it at less than five minutes. At that speed it is next to impossible to stop ransomware propagating throughout an IT system using manual methods.